(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This systematic literature review examines the Adaptive Reuse Potential (ARP) Model and its application in developing age-friendly social housing. The study synthesizes research on the ARP Model's components, benefits, and variations, focusing on its relevance to repurposing existing buildings for social housing. Our findings reveal that the ARP Model offers a robust framework for assessing buildings' suitability for adaptive reuse, with significant potential for promoting sustainable urban development and creating age-friendly living environments. The model's consideration of multiple obsolescence factors allows for a comprehensive evaluation of a building's adaptive reuse potential. Variations of the model, including the Green Adaptive Reuse Model and the Adaptive Sustainable Reuse Model, further enhance its applicability to age-friendly social housing development by incorporating additional sustainability and decision-making criteria. By critically analyzing existing literature, we highlight the model's strengths in addressing complex urban regeneration challenges and meeting the evolving needs of aging populations. The ARP Model demonstrates particular efficacy in bridging architectural preservation with contemporary social housing requirements, offering a nuanced approach to repurposing underutilized urban spaces. This comprehensive evaluation underscores the importance of interdisciplinary considerations in adaptive reuse strategies, integrating architectural, social, and environmental perspectives. This review concludes that the ARP Model and its variations provide valuable tools for decision-making in adaptive reuse projects, particularly in addressing the growing demand for age-friendly social housing. However, there is scope for further development of the model to more explicitly incorporate age-friendly design principles.